TRAÇOS DE PERSONALIDADE E ACIDENTES COM MOTOCICLISTAS NO CONTEXTO URBANO - Romero, Daniel Luiz Romero (2017)
The morbimortality caused by accidents involving transit riders has been gaining prominence on the world scene. It is attributed this to various aspects, as for example, the adoption of risk behaviors, lack of attention, exacerbated confidence, in addition to the attraction of motorcyclists by risk and in terms of the aspects related to personality. The objective of this study was to evaluate the association between personality characteristics (factors of temperament and character) and risk of accidents of motorcycles. The sample in this study was 153 riders from 18 to 60 years of age, both genders, different levels of education and who use the motorcycle in its activities. It was verified the frequency regarding gender, age, level of education, marital status, knowledge of the course of defensive driving, as well as did the course, where the use of a motorcycle (professional, daily travel and leisure) time of empowerment, practice time round mileage per day, number of accidents, reasons of accidents and consequences of accidents to health and the factors of the personality through the inventory of temperament and character of Cloniger (TCI). The results show a higher prevalence of males (75.8%) and that the main reasons of accidents has a relationship with attitudes such as traveling at high speed, breaking traffic laws, recklessness, and bad conditions of roads that have provided 43.8% of accidents. As to the consequences of accidents to the health of motorcyclists, 43.1% suffered some type of fracture, 78.4% had light bruises, 75.8% using the motorbike for daily shifts and only 37.3% of the sample did courses in defensive driving. As for the characteristics of the personality, you can point to the adoption of a risk behavior associated with high scores in the factor search of Novelty Seeking (NS), as well as low score in factor Harm Avoidance (HA) when compared with the expected average for the population (NS = 20.29, P = 0.001 and HA = 14.96, P = 0.006). These personality traits show traits of impulsivity, excessive confidence in situations of danger and optimism unrealistic in the face of potentially severe. It was observed in this study that the greater the distance round per day, the greater the number of accidents among motorcyclists in this sample, as well as that there is a significant difference between the averages of mileage round by those who make professional use of motorcycle and who doesn't, Motoboy and not Motoboy. This group also presents reduced scores in the factor of temperament Harm Avoidance, as well as a strong tendency to increase the score on a factor for Novelty Seeking. Thus, the temperamental characteristics in addition to the time of exposure corroborate so that motoboys are more likely to suffer accidents.